2021
DOI: 10.18203/2394-6040.ijcmph20213788
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility pattern of Klebsiella species isolated from various clinical samples in a tertiary care hospital Coimbatore

Abstract: Background: The genus Klebsiella of Enterobacteriaceae family is ubiquitous in nature. They cause many nosocomial infections like pneumonia, urinary tract infections, wound infections, bacteremia and septicemia. Multidrug resistance is seen in Klebsiella which serves as the most common cause of increased morbidity and mortality. This study reveals the prevalence and antibiotic sensitivity pattern of Klebsiella species from various clinical samples. The primary objectives are as follows: To isolate and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…The highest isolation rate of Klebsiella species, about 36.10%, was in the surgery department, followed by medicine (24.40%), obstetrics and gynecology (13.20%), pediatrics (11.70%), orthopedics and outpatient department (6.30%), and ENT (1.80%). Vijayashree et al also found highest isolate from department of surgery [13].…”
Section: Discussionmentioning
confidence: 90%
“…The highest isolation rate of Klebsiella species, about 36.10%, was in the surgery department, followed by medicine (24.40%), obstetrics and gynecology (13.20%), pediatrics (11.70%), orthopedics and outpatient department (6.30%), and ENT (1.80%). Vijayashree et al also found highest isolate from department of surgery [13].…”
Section: Discussionmentioning
confidence: 90%